2011
DOI: 10.1155/2011/319624
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Single- and Few-Layer Graphene Sheets Using Co Deposition on SiC Substrate

Abstract: Single- and few-layer graphene sheets were fabricated by selective chemical reactions between Co film and SiC substrate. A rapid cooling process was employed. The number of layers and crystallinity of graphene sheets were controlled by process parameters. The formation mechanism of graphene was highly sensitive to carbon diffusion. Free carbon precipitated and then moved across the product layer that was composed mainly of cobalt-silicides. The graphene layer formed homogeneously on the surface and then transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Therefore, Si atoms will be sublimated and the graphitization will be able to occur, where the C atoms on the top of surface are rearranged to synthesize the epitaxial graphene 4,[16][17][18][19] . In order to create alternative processes, some studies have shown that the addition of a layer of "catalyst material" (such as Ni or Co) promotes the reduction of the temperature required for SiC decomposition [23][24][25][26] . Nevertheless, despite SiC dissociation is promoted in this case, the Si sublimation does not occur; rather a chemical reaction to form a silicide phase between the catalyst material and Si happens.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Si atoms will be sublimated and the graphitization will be able to occur, where the C atoms on the top of surface are rearranged to synthesize the epitaxial graphene 4,[16][17][18][19] . In order to create alternative processes, some studies have shown that the addition of a layer of "catalyst material" (such as Ni or Co) promotes the reduction of the temperature required for SiC decomposition [23][24][25][26] . Nevertheless, despite SiC dissociation is promoted in this case, the Si sublimation does not occur; rather a chemical reaction to form a silicide phase between the catalyst material and Si happens.…”
Section: Introductionmentioning
confidence: 99%
“…It can be deposited using selective chemical reactions between Co film and SiC. 50 High thermal conductivity of SiC would be essential for both emitter and collector containing graphene. The surface 1 [ Fig.…”
Section: Theoretical Analysis Of Performance Of Solar Thermionic Enermentioning
confidence: 99%
“…First stage (Figure 16a) represents the initial situation dealing with pre-deposition of the Ni film on the SiC surface. Another approach involves the use of cobalt as a catalytic metal to form graphene layers and to lower the growth temperature [150][151][152]. Generally, cobalt can also react with silicon and leads to the formation of cobalt silicide.…”
Section: Alternative Approaches To Graphene Synthesis On Sicmentioning
confidence: 99%
“…Generally, cobalt can also react with silicon and leads to the formation of cobalt silicide. Meanwhile, the silicidation reaction with Co participation requires higher temperatures, compared with that by Ni [150]. Nevertheless, it is believed that such conditions can be favorable to lower the number of defects during the graphene formation and to improve the graphene quality [150].…”
Section: Alternative Approaches To Graphene Synthesis On Sicmentioning
confidence: 99%
See 1 more Smart Citation